A fault-tolerant enhancement of routing protocol for wireless sensor network - Che-Aron, Zamree (Kulliyyah of Engineering, International Islamic University Malaysia, 2010)
As more and more real Wireless Sensor Network's (WSN) applications are tested and deployed over the last decade, the research community of WSN realizes that several issues need to be revisited from practical angles, such as reliability and availability. Furthermore, fault-tolerance is one of the main issues in WSNs since it becomes critical in real deployed environments where network stability and reduced outage times are important. Basically, wireless sensor networks suffer from resource limitations, high failure rates and faults caused by the defective nature of wireless communication and the wireless sensor itself. This can lead to situations, where nodes are often interrupted during data transmission and blind spots occur in the network by isolating some of the devices. In this thesis report, we address the reliability issue by designing and developing an enhanced fault-tolerant mechanism for Ad hoc On- Demand Distance Vector (AODV) routing protocol. It can be used in WSN and called the ENhanced FAult-Tolerant AODV (ENFAT-AODV) routing protocol. The proposed ENFAT-AODV routing protocol improves the reliability and robustness of the network by creating a backup path for every node on a main path of data delivery. When a node gets failure to transmit a data packet through the main path, it immediately utilizes its backup route to become a new main path for the transmission of next coming data packets without any interruption. As compared to the original AODV, from the simulation results, ENFAT-AODV reduces the number of dropped data packets and maintains the continuity of data packet transmission in presence of network faults. Furthermore, at high failure rate, it improves the throughput, reduces the average End-to-End delay, the average jitter and the control overhead in the network. Therefore, the results prove that the proposed ENFAT-AODV routing protocol enhances the original AODV in term of the reliability, availability and faulttolerant ability of the network. However, the ENFAT-AODV performs well in the static or very low movement network and produces more.